The Author as Annotator Ambiguities of Self-Annotation in Pope and Byron - Lahrsow, Miriam (Brill, 2022)
What literary and social functions do self-annotations (i.e. footnotes and endnotes that authors appended to their own works) serve? Focussing on Alexander Pope's Dunciads and a wide selection of Lord Byron's poems, Lahrsow shows that literary self-annotations rarely just explain a text. Rather, they multiply meanings and pit different voices against each other. Self-annotations serve to ambiguate the author's self-presentation as well as the genre, tone, and overall interpretation of a text. The study also examines how notes were employed for 'social networking' and how authors used self-annotations to address, and differentiate between, various groups of readerships. Additionally, the volume sheds light on the wider literary and cultural context of self-annotations: How common were they during the long eighteenth century? What conventions governed them? And were they even read? The study hence combines literary analysis with insights into book history and the history of reading.